Characterisation of Colour Components and Polymeric Pigments of Commercial Red Wines by Using Selected UV-Vis Spectrophotometric Methods - Versari, A. Versari; Parpinello, G.P.; Mattioli, A.U. (South African Journal of Enology and Viticulture, 2016)
The composition of the colour components of commercial red wines from Italy was analysed in terms of total colour, co-pigmentation, SO2-resistant pigments, small and large polymeric pigments, and tannins. A total of 128 wines, including Sangiovese, Cabernet Sauvignon, Nero d’Avola, Merlot, Marzemino, Negroamaro, Aglianico, Cannonau and Rossese di dolceacqua from five vintages (1999 to 2003) were analysed. The composition of the wines showed significant differences in terms of total colour and co-pigmentation. Total colour at 520 nm was highest in Marzemino (7.50±1.5 AU, absorbance units), and then in Aglianico (7.10±2.8 AU) and Cabernet Sauvignon (5.01±2.50 AU). The level of large and small polymeric pigments in Sangiovese wines showed a range from 0.05 to 0.40 and 0.10 to 0.27 AU 520 nm respectively. The variation in the level of polymeric pigments is affected by a number of factors, including vintage, grape composition, fermentation and storage conditions.